Covid 19 Pandemic: Enhancing Customer Loyalty to The Existence of Traditional Market - Zaky Putra Pratama; Dessy Kurnia Sari; Donard Games; Tedi Hidayat (Institute of Computer Science (IOCS), 2021)
Observations were conducted to clarify the alleged problem, in which identified problems such as seller friendliness in transactions, personal service, and price fluctuations still unsportsmanlike, and it became triggers for customers to switch and following modern markets offered. This paper aims to examine the effect of service quality and price to enhancing customer loyalty in traditional market, through customer satisfaction. By using purposive as sampling technique and screening method to ensure our target. Our questionnaires in online form, and 82 feedbacks received. The data was analyzed by assisting PLS Software Vs 3.3. We found customer satisfaction significantly contributes to the relationship between service quality and price on customer loyalty partially mediated. This contribution strongly supports the previously insignificant effect of price on loyalty of traditional market customers